2005
DOI: 10.1111/j.1540-8159.2005.09382.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Optimization of Pacing Sensors Improves Exercise Capacity without Influencing Quality of Life

Abstract: After 1 month of individual optimization of rate response pacemakers, exercise capacity was improved and maximum HR increased, although QOL remained unchanged. Accessible pacemaker sensor algorithms are mandatory for individual optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…This blending principle allows the MV sensor to drive the sensor-indicated rate after exercise is initiated and has been shown to restore chronotropic competence 26. Sensor optimization with RAP is important 35, therefore implanted patients will perform a hall walk to optimize sensor settings prior to undergoing the 1 mo. exercise test evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…This blending principle allows the MV sensor to drive the sensor-indicated rate after exercise is initiated and has been shown to restore chronotropic competence 26. Sensor optimization with RAP is important 35, therefore implanted patients will perform a hall walk to optimize sensor settings prior to undergoing the 1 mo. exercise test evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…The APPROPRIATE study will also attempt to limit RV pacing in order to isolate the evaluation of sinus node function. Finally, previous studies [10,18,19] have demonstrated that manufacturer determined nominal sensor settings may be too conservative to provide appropriate heart rate response during exercise. These findings strongly suggest that individual patient optimization of the sensors is important to achieve optimal results.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies [10,18,19] have demonstrated that manufacturer determined nominal sensor settings may be too conservative to provide appropriate heart rate response during exercise, suggesting that the optimization of the sensors for each patient is important to achieve optimal results. Furthermore, it is possible that previous studies that have evaluated the effects of rate-modulated pacing may have not studied patient groups with true chronotropic incompetence.…”
Section: Introductionmentioning
confidence: 98%
“…Shaber et al confirmed that conservative or nominal rate responsive settings may be suboptimal for many patients and that rate response optimization should be considered 38 . Further, exercise capacity and maximum heart rate were improved following 1 month of individual rate response optimization despite QOL remaining unchanged compared to patients with default sensor settings 39 …”
Section: Discussionmentioning
confidence: 99%